Effect of linseed and sunflower oil supplementation in the diet on health beneficial fatty acids in intramuscular fat of lambs - Janíček, Martin; Margetín, Milan; Vavrišínová, Klára; Juhás, Peter; Hozáková, Katarína (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2020)
The effect of linseed and sunflower oil on health beneficial fatty acids composition of Musculus longissimus lumborum et thoracis (MLLT) of lambs was investigated. Thirty slovak dairy sheep breed ram lambs (20.11±3.06 kg) randomly allocated into three groups were fed a control diet (C) composed by 70 % concentrate and 30 % forage and two expeimental diets (5% linseed oil and 5% sunflower oil, LO and SO respectively). The experimental period was 46 days and lambs were slaughtered at 28.83±3.88 kg. Differences between dietary groups were calculated using General Linear Model of SAS 9.3. Addition of linseed oil, rich in α-linolenic acid (C18:3n-3) significantly increased rumenic acid (c9,t11-C18:2; P<0.01), C18:3n-3 (P<0.001), eicosapentaenoic acid (C20:5n-3; P<0.001), docosahexaenoic acid (C22:6n-3; P<0.05), conjugated linoleic acid (CLA; P<0.01) and decreased n-6/n-3 ratio (P<0.001). The addition of SO to the diet did not influence significantly essential and health beneficial fatty acids in lamb meat. The results of the present study suggest that linseed oil supplementation can be safely incorporated in the diets of lambs to enrich lamb meat with essential and healthy fatty acids.